2006
DOI: 10.1021/ie051453l
|View full text |Cite
|
Sign up to set email alerts
|

Simulated and Experimental Dispersed-Phase Breakage and Coalescence Behavior in a Kühni Liquid−Liquid Extraction ColumnSteady State

Abstract: Given the difficulties normally associated with direct experimentation in liquid-liquid extraction processes, their direct computer simulation has acquired increased relevance and utility, especially when dealing with some of the details of the dispersed-phase hydrodynamics. The possibility of testing very complex theoretical models of such behavior is increasingly attractive to the researcher, as a result of both the power and the availability of personal computing resources. Experimental data obtained in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, the correlation has two adjustable parameters that need to be fitted using experimental data. For some known column types, geometry and the chemical system, the adjustable parameters are given in literature [36][37][38].…”
Section: Coalescencementioning
confidence: 99%
“…However, the correlation has two adjustable parameters that need to be fitted using experimental data. For some known column types, geometry and the chemical system, the adjustable parameters are given in literature [36][37][38].…”
Section: Coalescencementioning
confidence: 99%
“…More work involving data acquisition when mass transfer occurs is therefore still needed, involving the determination of solute concentration profiles and of their effects on the dispersion's interacting behavior and the ensuing local dispersedphase hold-ups and drop diameters. This is deemed essential to thoroughly identify the detailed phenomenologies that the newest models and algorithms 14…”
Section: Introductionmentioning
confidence: 99%
“…More work involving data acquisition when mass transfer occurs is therefore still needed, involving the determination of solute concentration profiles and of their effects on the dispersion’s interacting behavior and the ensuing local dispersed-phase hold-ups and drop diameters. This is deemed essential to thoroughly identify the detailed phenomenologies that the newest models and algorithms must also directly address and successfully describe in the end. The collection and classification of this experimental information when mass transfer occurs was thus the main objective of this work.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] In ADM, the product of mass transfer coefficient and interfacial area is simplified as a constant through the height of the column. 23 However, experimental results have demonstrated that the dispersed phase holdup and drop size in contactors vary significantly along the column height, 3,[24][25][26] which not only leads to a longitudinal variation of specific interfacial area but also affects axial distribution of the mass transfer coefficient. 27 Consequently, more reliable theoretical methods for predicting mass transfer behavior are needed in the designing and scaling-up of such extractors.…”
mentioning
confidence: 99%